2021
DOI: 10.1155/2021/7351470
|View full text |Cite
|
Sign up to set email alerts
|

An Apple Detection Method Based on Des-YOLO v4 Algorithm for Harvesting Robots in Complex Environment

Abstract: Real-time detection of apples in natural environment is a necessary condition for robots to pick apples automatically, and it is also a key technique for orchard yield prediction and fine management. To make the harvesting robots detect apples quickly and accurately in complex environment, a Des-YOLO v4 algorithm and a detection method of apples are proposed. Compared with the current mainstream detection algorithms, YOLO v4 has better detection performance. However, the complex network structure of YOLO v4 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A class loss function based on AP-Loss (Average Precision loss) is proposed to deal with the positive and negative sample imbalance problem during training. The final experimental results show that the mAP of the improved algorithm is 97.13% ( Chen et al., 2021 ). An improved YOLOv5 model was proposed to improve the detection of kiwi defects by adding a small target layer, introducing SE attention mechanism and CIoU loss function, and the mAP of the improved model was improved by nearly 9% compared with the original model ( Yao et al., 2021 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A class loss function based on AP-Loss (Average Precision loss) is proposed to deal with the positive and negative sample imbalance problem during training. The final experimental results show that the mAP of the improved algorithm is 97.13% ( Chen et al., 2021 ). An improved YOLOv5 model was proposed to improve the detection of kiwi defects by adding a small target layer, introducing SE attention mechanism and CIoU loss function, and the mAP of the improved model was improved by nearly 9% compared with the original model ( Yao et al., 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…A multi-scale parallel algorithm MP-YOLOv3 was proposed to improve the detection of tomato gray mold based on the MobileNetv2-YOLOv3 model (Wang and Liu, 2021a), and the experimental results showed that the improved model has strong robustness in real natural environments. An algorithm based on super-resolution image enhancement (Zhu et al, 2021) and an algorithm combining Inception and an improved Softmax classifier are proposed to detect grape and apple diseases, respectively (Li et al, 2022). Enhancing feature extraction by incorporating DenseNet interlayer density in the YOLOv4 model (Gai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [20] constructed a new apple leaf disease detection model called MEAN-SSD, which achieved 83.12 % mAP detection performance and operated at a detection speed of 12.53 FPS. The complex network structure of YOLOv4 will reduce the efficiency of the apple picking robot, Chen et al [21] proposed a Des-YOLO structure to reduce network parameters and improve the detection speed of the algorithm. Wang et al [22] made lightweight improvements to YOLOv5s model channel pruning, the improved model has an accuracy of 95.8% and a size of only 1.4 MB.…”
Section: Introductionmentioning
confidence: 99%
“…YOLOv4 is state of the art in object detection which is the result of the development of YOLOv3 research [ 18 ] and has been tested in agriculture with satisfactory results such as automating pear counting [ 12 ], apple detection [ 19 ] and citrus fruit ripeness detection [ 20 ]. YOLOv4 employs a DarkNet framework based on the low-level programming language to do fast computing, which is ideal for implementing conditions in real time.…”
Section: Introductionmentioning
confidence: 99%